Pirólise orientada de lodo de esgoto para aplicação em solos agrícolas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The treatment of sanitary sewage generates sewage sludge, which is difficult to dispose of because it contains pathogens, potentially toxic elements and pollutants. The present research suggests the destination of this residue to agricultural soils in the form of biochar, which is the solid product of pyrolysis, being based on thermal decomposition in an inert atmosphere with temperature selected according to the desired characteristics. Therefore, it was aimed i) to build a pilot-scale pyrolyzer, ii) to select a target soil for biochar application by guiding pyrolysis through the properties of its colloids, iii) to perform a biochar incubation experiment to quantify the effects on water and nutrient availability of the target soil, iv) to implement biochar dose experiments in no-till soils to determine the optimal dose that improves its functions in making water and nutrients available to plants and that sequester carbon. A prototype- scale pyrolyzer was developed that made it possible to control the temperature with accuracy and precision and a pyrolysis process that is safe for the operator and that starts from the pretreatment of sewage sludge to the control of production variability. Final pyrolysis temperatures of 300 °C, 400 °C and 500 °C were tested and the effects on biochar characteristics were evaluated. Pyrolysis at 300 °C resulted in the highest cation exchange capacity and C content through the maintenance of volatile material and surface functional groups, giving the biochar higher surface electrical charge, higher water retention, lower hydrophobic resistance and higher metal solubility compared to the biochar obtained at the other temperatures. When incubating the biochar obtained in this study and another from Brasilia in a Cambissolo with colloids of low chemical reactivity at a dose equivalent to 10 Mg ha-1 , promising results were obtained from the biochar obtained at 300 °C, causing an average increase of 20% of the water easily available to plants and an increase in soil P. When conducting two field experiments using doses of biochar obtained at 300 °C, there was an effect on wheat productivity when biochar at a dose of 5 Mg ha-1 was applied to a Neossolo with 87% sand content, surpassing the chemical fertilization used as a farm standard. When the biochar was applied in the field in the same Cambissolo used in the incubation test, there was no influence on plant productivity, possibly due to liming and organic fertilization recently performed in this soil. It is concluded that the prototype and the pyrolysis process presents high reproducibility, allowing the recovery of volatiles with biofuel potential; that the biochar produced from sewage sludge presented promising characteristics to be applied to agricultural soils with low potential environmental impacts; that the targeted pyrolysis of biochar allowed to obtain beneficial effects on soil water availability and its P content and that in the field it was possible to observe expressive results when using biochar as a substitute for fertilization in a soil highly dependent on the use of inputs to sustain plant production and also sequester carbon.
Keywords: Termoconversão; Resíduos; Valorização; Disponibilidade hídrica; Química de superfície; Thermoconversion; Waste; Valorization; Water availability; Surface chemistry.; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA